Parental Effects and Reproductive Potential of Fish and Marine Invertebrates: Cross-Generational Impact of Environmental Experiences - Rosario Domínguez-Petit; Cristina García-Fernández; Ezequiel Leonarduzzi; Karina Rodrigues; Gustavo Javier Macchi (Fishes, 2022)
The reproductive success of aquatic animals depends on a complex web of relationships between the environment, the attributes of the reproductive individuals and human-induced selection. All of them are manifested directly or indirectly through parental effects, which can also compensate for certain external impacts. Parental effects refer to the influence that the phenotype and environmental conditions in which individuals develop exert on the phenotype of their offspring, and they can even have transgenerational impact. This paper describes the different types of parental effects and reviews the published literature to analyze the causes of their variation and their impact on reproductive resilience and population dynamics.